Demonstration Method: Concrete Innovation Increases Student Learning Motivation - Ghina Agniya; Mochamad Arsad Ibrahim; Imam Tabroni; Siti Nuriyah Nurhadi; Suhartini (International Journal of Integrative Sciences, 2022)
In the fiqh learning process at MI As-Sakinah, various learning methods are needed and are in accordance with the subject matter that will be taught by the teacher. One of the learning methods is using the demonstration method. Various methods or techniques for presenting learning materials can be used by teachers in teaching and learning activities. In this study, researchers used one of the true experimental design forms, namely the Pretest-Posttest Control Group Design . In this design, there are two groups that are randomly selected, then given a pretest to find out whether there is a difference in the initial state between the experimental group and the control group. The pretest results are good if the experimental group scores are not significantly different